1995
DOI: 10.1002/cne.903520108
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical identification of neurons in ganglia of the guinea pig sphincter of oddi

Abstract: The sphincter of Oddi is a smooth muscle sphincter that regulates the flow of bile into the duodenum. To identify potential chemical coding in sphincter of Oddi neurons, immunohistochemistry and histochemistry were employed to assay for putative neurotransmitters and related synthetic enzymes in wholemount preparations, with and without colchicine treatment. Immunoreactivities for enkephalin-endorphin (ENK-END), substance P (SP), nitric oxide synthase, vasoactive intestinal peptide (VIP), neuropeptide Y (NPY),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Recombinant human hemoglobin may alter the motor function of the sphincter of Oddi in vitro and in vivo by binding endogenous NO (Cullen et al, 1996). Neurons containing nNOS immunoreactivity or NADPH diaphorase were histochemically detected in the sphincter of Oddi of the human, monkey (De Giorgio et al, 1994), dog (Tanobe et al, 1995), guinea pig (Wells et al, 1995), and possum (Baker et al, 1993;Simula et al, 2001). The presence of NOS has also been demonstrated in the gall bladder and biliary pathways of the guinea pig (Grozdanovic et al, 1994), monkey, and human (De Giorgio et al, 1994;Uemura et al, 1997).…”
Section: E Sphincter Of Oddi and Gall Bladdermentioning
confidence: 98%
“…Recombinant human hemoglobin may alter the motor function of the sphincter of Oddi in vitro and in vivo by binding endogenous NO (Cullen et al, 1996). Neurons containing nNOS immunoreactivity or NADPH diaphorase were histochemically detected in the sphincter of Oddi of the human, monkey (De Giorgio et al, 1994), dog (Tanobe et al, 1995), guinea pig (Wells et al, 1995), and possum (Baker et al, 1993;Simula et al, 2001). The presence of NOS has also been demonstrated in the gall bladder and biliary pathways of the guinea pig (Grozdanovic et al, 1994), monkey, and human (De Giorgio et al, 1994;Uemura et al, 1997).…”
Section: E Sphincter Of Oddi and Gall Bladdermentioning
confidence: 98%
“…As already mentioned, SP and CGRP are expressed by many nerve terminals supplying the MDP/SO in the guinea pig (Wells et al 1995) and pig (Sand et al 1993). Large number of SP-positive nerve fibres associated with the SO have been also found in the cat (Feher et al 1995).…”
Section: The Distribution and Chemical Coding Of Neuronsmentioning
confidence: 89%
“…These CGRP and/or SP-positive fibres have been suggested by the authors to represent sensory nerve terminals of extrinsic origin. Talmage et al (1997) have performed investigations dealing with the identification of cholinergic neurons in guinea pig SO ganglia, thus complementary to those carried out by Wells et al (1995). Based on the results of these two studies it can be concluded that about 69% of the neurons within the guinea pig SO ganglia are immunoreactive for ChAT thus can be classified as cholinergic nerve cells .…”
Section: Intrinsic Innervation Of the Sphincter Of Oddi (Fig 1)mentioning
confidence: 99%
See 2 more Smart Citations